Medial meniscus extrusion is invariably observed and consistent with tibial osteophyte width in elderly populations: The Bunkyo Health Study - Negishi, Yoshifumi; Kaneko, Haruka; Aoki, Takako; Liu, Lizu; Adili, Arepati; Arita, Hitoshi; Hada, Shinnosuke; Momoeda, Masahiro; Huang, Hui; Tomura, Jun; Wakana, Suguru; Shiozawa, Jun; et al. (Scientific reports, 2023)
We reported that the full-length width of medial tibial osteophytes comprising cartilage and bone parts correlates with medial meniscus extrusion (MME) in early-stage knee osteoarthritis (OA). However, no data exist on the prevalence of MME and its relationship with osteophytes in the elderly population. 1191 elderly individuals (females 57%; 72.9 years old on average) in the Bunkyo Health Study underwent standing plain radiograph and proton density-weighted MRI on knee joints. MRI-detected OA changes were evaluated according to the Whole-Organ Magnetic Resonance Imaging Score. A new method of assessing the cartilage and bone parts of osteophytes was developed using pseudo-coloring images of proton density-weighted fat-suppressed MRI. Most subjects showed Kellgren-Lawrence grade 1 or 2 radiographic medial knee OA (88.1%), MME (98.7%, 3.90 ± 2.01 mm), and medial tibial osteophytes (99.3%, 3.27 ± 1.50 mm). Regarding OA changes, MME was closely associated with the full-length width of medial tibial osteophytes (β = 1.114; 95% CI 1.069–1.159; p < 0.001) in line with osteophyte width (intraclass correlation coefficient, 0.804; 95% CI 0.783–0.823). Our data revealed that MME and medial tibial osteophytes are observed in the elderly and demonstrate that the degree of MME is consistent with the full-length width of medial tibial osteophytes, suggesting that osteophytes might be implicated in MME.